Pengaruh Pemberian Musik Klasik Terhadap Post Partum Blues Pada Ibu Primipara - Suganda, Yohana; Fitri, Dania (Universitas Sumatera Barat, 2023)
Improving maternal and infant health is a priority for health development in Indonesia. These improvements are directed at physical and psychological health. Psychological problems of primiparous postpartum mothers include postpartum blues which is one of the factors that contributes to maternal health indirectly. Classical music can stimulate the sympathetic and parasymptomatic nerves to produce a relaxation response. This research aims to determine the effect of providing classical music therapy on postpartum blues symptoms in primiparous mothers at the Independent Midwife Practice (PMB) Sri Wahyu Oktaviani AR, STr.Keb. This type of quasi-experimental research uses a nonequivalent control group design approach that uses two groups of research subjects, namely the experimental group 16 respondents before being given (Pretest) and after being given (Posttest). The statistical tests used were the Wilcoxon test and the Maan-Whatney test. The results showed that the postpartum blues symptom score of primiparous mothers in the experimental group after classical music intervention had a mean of 1.50. The results of the Maan-whatney test obtained a p value of 0.00